Intranasal monoclonal antibodies to mugwort pollen reduce allergic inflammation in a mouse model of allergic rhinitis and asthma - Tabynov, Kairat; Nedushenko, Igor; Tailakova, Elmira; Sergazina, Akbota; Bolatbekov, Turlan; Fomin, Gleb; Nurpeissov, Tair; Vaghasiya, Utsav; Petrovsky, Nikolai; Demyanov, Anton; Lebedin, Yuri; Tabynov, Kaissar (Frontiers in Immunology, 2025)
IntroductionAllergen-specific monoclonal antibodies (mAbs) have recently emerged as promising tools in allergy therapy, particularly for patients who do not respond adequately to allergen-specific immunotherapy (AIT). While previous studies have explored systemic delivery routes, the efficacy of local intranasal administration of allergen-specific mAb remains largely unexplored. Artemisia vulgaris pollen is among the top global aeroallergens, strongly associated with seasonal allergic rhinitis and asthma.MethodsHybridoma-derived murine IgG1 mAb specific to A. vulgaris pollen extract were generated and screened in vitro for their ability to block both mouse and human IgE binding to crude pollen extract and its major allergen, Art v 1. A lead mAb candidate was selected for in vivo evaluation using a BALB/c mouse model of allergic airway inflammation. The mAb was administered intranasally one hour prior to each of three consecutive allergen challenges. Clinical symptoms, airway hyperresponsiveness (AHR), lung cytokine profiles, and histopathological changes in nasal and lung tissues were assessed.ResultsFive IgG1 mAb recognising A. vulgaris extract were generated, with clone XA19 being the most potent, with high-affinity binding and IgE-blocking activity for both pollen extract (18-22% inhibition) and recombinant Art v 1 protein (52% inhibition). Intranasal pretreatment with XA19 prior to allergen challenge in pre-sensitised mice resulted in significant suppression of the ear swelling response, rhinitis symptoms, AHR, and lung and nasal turbinate inflammation. Pulmonary levels of Th2 cytokines (IL-4 and IL-5) were markedly reduced in mAb-pretreated mice, while total serum IgE levels remained largely unaffected.ConclusionIntranasal delivery of allergen-specific mAbs represents a novel, non-invasive strategy to prevent both upper and lower airway allergic inflammation. Our findings establish proof-of-concept for this approach and warrant further development.